Laboratory running test vs. field roller skiing test in cross-country skiers: A longitudinal study - Verges, S.; Flore, P.; Laplaud, D.; Guinot, M.; Favre-Juvin, A. (International Journal of Sports Medicine, 2006)
Laboratory treadmill running tests are commonly used to assess the effect of training programs and to prescribe training intensity for cross-country skiers. The present study compared the physiological parameters during a treadmill running (R) test and a field roller skiing (RS) test both at the beginning (Beg) and at the end (End) of a 6-month specific training program in seven competitive cross-country skiers. Oxygen uptake (V·O2) and blood lactate concentration ([La]) were assessed for exercise intensity corresponding to 70 %, 80 %, 90 % of maximal heart rate (HRmax) and to HRmax. V·O2 was lower for the RS test compared to the R test at any HR levels at Beg only (p < 0.05). Maximal V·O2 increased from Beg to End for the RS test only (+ 23.7 ± 10.4; p < 0.05). [La] was lower for the R test compared to the RS test during both testing periods at 90 % HRmax (p < 0.05), and no significant modification in [La] from Beg to End at any HR levels was observed (p > 0.05). The [La]/V·O2 curve shifted toward the right from Beg to End to a greater extent for the RS test compared to the R test. The present study emphasised the importance of exercise specificity in order to assess the effect of specific training program in competitive cross-country skiers.